Modelling study of the low-pump-power demand constructal T-shaped pipe network for a large scale radiative cooled-cold storage system. (25th December 2017) - Zhang, Kai; Zhao, Dongliang; Zhai, Yao; Yin, Xiaobo; Yang, Ronggui; Tan, Gang
Highlights: Novel radiative cooled-cold storage system is proposed to provide supplemental cooling for air-cooled power plants. Head loss and heat loss analysis models for scalable constructal T-shaped pipe network are developed. The low-pump-power demand pipe network is designed for the 200-kWth RadiCold storage system and its performance is analyzed. Abstract: To provide supplemental cooling to air cooled condenser (ACC) based thermo-electric power plants, radiative cooling is one of the options to ensure comparable efficiency as water cooled power plants. However, radiative cooling has relatively low energy intensity, about 100 W/m 2 cooling power on daily average. To work with power plants generally at few hundreds of megawatts, an intermediate system is needed to bridge this huge energy intensity mismatching at low energy cost. A low-pump-power demand pipe network is proposed to collect cold energy generated by the radiative cooling surfaces using water as the heat transfer fluid and the cold water is thus stored in intermediate storage devices. In this work, head loss and heat loss analysis models have been developed for the proposed constructal T-shaped network design, which provides convenience to integrate and scale up the radiative cooling modules to a large system to meet megawatt power plant's supplemental cooling demand. A large radiative cooling system may consist of hundreds to thousand radiative cooled-cold (RadiCold) storage subsystems at a size of about 200-kWth each. Design of the 200-kWth RadiCold subsystem with constructal T-shaped network shows 11 kWh/day for pump electricity consumption and delivers cold energy of 4096 kWth /day.